The Future of the Professions How Technology Will Transform the Work of Human Experts - Richard Susskind, Daniel Susskind (USA - OSO Oxford University Press, 2022)
With a new preface outlining the most recent critical developments, this updated edtion of The Future of the Professions predicts how technology will transform the work of doctors, teachers, architects, lawyers, and many others in the 21st century, and introduces the people and systems that may replace them
Keywords: Technological innovations